14-3-3ζ delivered by hepatocellular carcinoma-derived exosomes impaired anti-tumor function of tumor-infiltrating T lymphocytes - Wang, Xiaochen (Cell Death Dis, 2018)
Increasing evidence shows that the anti-tumor functions of tumor-infiltrating T lymphocytes (TILs) were inhibited significantly, but the underlying mechanisms remain not fully understood. In this study, we found that 14-3-3ζ expression was up-regulated in hepatocellular carcinoma (HCC) cells and in TILs. TILs with 14-3-3ζ high-expression (14-3-3ζ(high)) exhibited impaired activation (CD69), proliferation (Ki67) and anti-tumor functions compared to 14-3-3ζ low expression (14-3-3ζ(low)) TILs. Flow cytometry assay showed that compared with 14-3-3ζ(low) CD8(+)T cells, 14-3-3ζ(high) ones exhibited higher frequency of exhausted phenotypes as measured by inhibitory receptors such as PD-1, TIM-3, LAG3, and CTLA-4. 14-3-3ζ overexpression inhibited the activity and proliferation of peripheral blood CD3(+) T cells, deviated the differentiation of naive T cells from effector T cells to regulatory T cells. Moreover, we found that 14-3-3ζ expression levels in TILs correlated positively with those in HCC cells. Naive T cells co-cultured with HCC cells or the visible components of culture medium of HCC cells exhibited increased 14-3-3ζ expression. Stochastic optical reconstruction microscopy (STORM) and confocal assay showed that 14-3-3ζ-containing exosomes derived from HCC cells could be swallowed by T cells, suggesting that 14-3-3ζ might be transmitted from HCC cells to TILs at least partially through exosomes. In conclusion, our study for the first time demonstrated that 14-3-3ζ is up-regulated in and inhibited the anti-tumor functions of tumor-infiltrating T cells in HCC microenvironment and that 14-3-3ζ might be transmitted from HCC cells to T cells at least partially through exosomes.